Big Data: potentially discriminatory factors in data analysis - Coneglian, Caio Saraiva [UNESP]; Santarem Segundo, Jose Eduardo; Goncalves Sant'ana, Ricardo Cesar [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2017)
The experienced technological changes from the turn of the century caused a revolution in the Big Data society, in which the data analysis to determine patterns and behaviors could use large amounts of data. It is possible to notice that some analyses in the context of the Big Data are being conducted to generate discriminatory results. This study aims to identify factors that can potentially lead to discrimination in the process of data analysis. The methodology used was qualitative, exploratory and bibliographical, enumerating the discrimination cases. As the result, we identified possibly discriminatory factors and we provided an explanation of these factors. Through research, we noticed the need of showing deep reflection about the results that are obtained from the data analysis and the need of Information Science approaching such questions, in order to point out the paths to be taken.
Keywords: Big data; Data analysis; Discrimination; Potentially discriminatory factors